Neuroprotective effects of adjunctive treatments for acute stroke thrombolysis: a review of clinical evidence. (2nd November 2017) - Zhou, Hongxing; Huang, Suyun; Sunnassee, Gavin; Guo, Weiyu; Chen, Jian; Guo, Yang; Tan, Sheng
ABSTRACT: The narrow therapeutic time window and risk of intracranial hemorrhage largely restrict the clinical application of thrombolysis in acute ischemic stroke. Adjunctive treatments added to rt-PA may be beneficial to improve the capacity of neural cell to withstand ischemia, and to reduce the hemorrhage risk as well. This review aims to evaluate the neuroprotective effects of adjunctive treatments in combination with thrombolytic therapy for acute ischemic stroke. Relevant studies were searched in the PubMed, Web of Science and EMBASE database. In this review, we first interpret the potential role of adjunctive treatments to thrombolytic therapy in acute ischemic stroke. Furthermore, we summarize the current clinical evidence for the combination of intravenous recombinant tissue plasminogen activator and various adjunctive therapies in acute ischemic stroke, either pharmacological or non-pharmacological therapy, and discuss the mechanisms of some promising treatments, including uric acid, fingolimod, minocycline, remote ischemic conditioning, hypothermia and transcranial laser therapy. Even though fingolimod, minocycline, hypothermia and remote ischemic conditioning have yielded promising results, they still need to be rigorously investigated in further clinical trials. Further trials should also focus on neuroprotective approach with pleiotropic effects or combined agents with multiple protective mechanisms.